Soil salinity aáeáment using directed soil sampling from a geophysical survey with electromagnetic technology: a case study - Amezketa, E.
(Es, En)
ilus., 22 ref.
Keywords: ALFALFA; SALINIDAD; MUESTREO; TECNICAS ANALITICAS; SENSORES; RIEGO; PROCESAMIENTO DE DATOS; ESPAÑA